Capital structure and firm financial performance in Vietnam. (2018) - Anh, Nguyen Huu; Duong, Doan Thuy; Yoon, Sung Wook
We investigate the relation between the capital structure and financial performance of 235 Vietnamese companies listed on the Ho Chi Minh Stock Exchange during 2011-2013. Ordinary least squares (OLS), fixed effect method (FEM) and random effect method (REM) are employed to address econometric issues and to improve the accuracy of the regression coefficients. Furthermore, the dynamic panel generalised method of moments (GMM) estimator is adopted to address the problems of endogeneity, unobservable heterogeneity and simultaneity. The results show that financial performance, measured by return on equity (ROE) and earning per share (EPS), has a statistically significant negative association with leverage level.